2011
DOI: 10.1016/j.physio.2010.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Master's level study: learning transitions towards clinical expertise in physiotherapy

Abstract: Background Evidence suggests that practitioners who successfully complete a UK Master's level course, accredited by the Manipulation Association of Chartered Physiotherapists (MACP), enhance their clinical practice and demonstrate attributes of clinical expertise. What remains unclear is the process by which practitioners change and enhance their practice. Greater understanding of the learning process would help to inform programme design and delivery, and enhance the quality of the educational experience and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 20 publications
(22 reference statements)
3
34
0
Order By: Relevance
“…In a number of studies, graduates reported improvement in the clinical care they provided [22,42-46] and in their attitude towards patients [43,47]. Alumni also reported enhanced self-confidence [22,23,29,37,43,48,49]. …”
Section: Resultsmentioning
confidence: 99%
“…In a number of studies, graduates reported improvement in the clinical care they provided [22,42-46] and in their attitude towards patients [43,47]. Alumni also reported enhanced self-confidence [22,23,29,37,43,48,49]. …”
Section: Resultsmentioning
confidence: 99%
“…This paper reports on practitioners' perceived learning outcomes following successful completion of an MACP approved MSc. These learning outcomes form part of a broader theory on the learning transition of practitioners reported elsewhere (Petty et al, 2010).…”
Section: Designmentioning
confidence: 92%
“…Furthermore, in taking a grounded theory approach, this research followed in the footsteps of researchers in the physiotherapy profession who used grounded theory to help understand clinical expertise and decision-making. 57e59, 72,73 The main methodological processes used in grounded theory (Fig. 1) are now discussed with reference to the case example.…”
Section: Resultsmentioning
confidence: 99%